Cover Picture: Complexity from Simplicity: Tricyclic Aziridines from the Rearrangement of Pyrroles by Batch and Flow Photochemistry (Angew. Chem. Int. Ed. 5/2013). Issue 5 (16th January 2013) - Maskill, Katie G.; Knowles, Jonathan P.; Elliott, Luke D.; Alder, Roger W.; Booker‐Milburn, Kevin I.
<x xml:space="preserve">Abstract</x> Complex tricylic aziridines can be prepared from simple pyrroles by UV irradiation. In their Communication on page 1499 ff., K. I. Booker‐Milburn and co‐workers show that the reaction proceeds by a two‐stage photochemical sequence that involves [2+2] cycloaddition and rearrangement, and that the scale of the reaction can be increased using a customized FEP flow reactor.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>